2020
DOI: 10.1002/ehf2.13125
|View full text |Cite|
|
Sign up to set email alerts
|

Individual patient data meta‐analysis of the effects of the CARILLON® mitral contour system

Abstract: Aims Functional mitral regurgitation (MR) (FMR) is common in heart failure with reduced ejection fraction and worsens morbidity and mortality, even when mild. The CARILLON® mitral contour system (Cardiac Dimensions, Kirkland, WA, USA), a mitral annuloplasty device delivered percutaneously to the coronary sinus, is designed to reduce the mitral annular dimension by virtue of the close anatomic relationship between the coronary sinus and the posterior mitral annulus. We performed a comprehensive individual patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
1
18
0
1
Order By: Relevance
“…A sham‐controlled randomized trial testing a transcatheter indirect mitral annuloplasty device met its primary endpoint of mitral regurgitant volume reduction with reverse LV and LA remodelling at 12 months 619 . Further studies confirmed favourable results on LA volumes and LV remodelling with trends towards improvement in mean 6MWT distance and symptoms and a reduction in HF hospitalizations in an IPD meta‐analysis 620–623 . Transcatheter mitral valve replacement is also emerging as a possible alternative option, but randomized trials are still lacking 624 …”
Section: Cardiovascular Comorbiditiesmentioning
confidence: 84%
“…A sham‐controlled randomized trial testing a transcatheter indirect mitral annuloplasty device met its primary endpoint of mitral regurgitant volume reduction with reverse LV and LA remodelling at 12 months 619 . Further studies confirmed favourable results on LA volumes and LV remodelling with trends towards improvement in mean 6MWT distance and symptoms and a reduction in HF hospitalizations in an IPD meta‐analysis 620–623 . Transcatheter mitral valve replacement is also emerging as a possible alternative option, but randomized trials are still lacking 624 …”
Section: Cardiovascular Comorbiditiesmentioning
confidence: 84%
“…Even a small mitral effective regurgitant orifice area contributes to LA remodelling on top of traditional systolic and diastolic parameters 180 . Percutaneous mitral valve annuloplasty may also effectively reduce mitral valve annulus and have favourable effects on LV remodelling and patients' symptoms 181,182 . Tricuspid regurgitation is highly prevalent in HF patients.…”
Section: Non‐pharmacological Therapiesmentioning
confidence: 99%
“…The core component of cardiac rehabilitation is the assessment of patient' class of risk [69] together with dietary advice [70,71], educational intervention [72,73], psychological support [74], exercise training [75] and therapy management [69]. Nowadays great progresses have been made in drug therapy [76][77][78][79][80], devices [81][82][83][84][85][86], and diagnostic technologies [87][88][89][90], which allow for an even greater reduction of some risk factors. However, to further reduce risk of new CV events, it is important to act not only on optimization of therapy and its adherence, but also on other risk factors such as OB and lifestyle [91][92][93].…”
Section: Exercise Training In Secondary CV Preventionmentioning
confidence: 99%